Introductory Note (Revista Lusófona de Educação, 2020)
The present dossier of Revista Lusófona de Educação results from a peer-review selection of the papers presented at the MILT conference - Media Literacy for Living Together: the future of media and learning in participation, held in June 26-28, 2019 at Lusófona University in Lisbon.